2017
DOI: 10.1021/acsnano.6b08260
|View full text |Cite
|
Sign up to set email alerts
|

Atomistic Origins of Surface Defects in CH3NH3PbBr3 Perovskite and Their Electronic Structures

Abstract: The inherent instability of CHNHPbX remains a major technical barrier for the industrial applications of perovskite materials. Recently, the most stable surface structures of CHNHPbX have been successfully characterized by using density functional theory (DFT) calculations together with the high-resolution scanning tunneling microscopy (STM) results. The two coexisting phases of the perovskite surfaces have been ascribed to the alternate orientation of the methylammonium (MA) cations. Notably, similar surface … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
95
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(104 citation statements)
references
References 45 publications
5
95
0
4
Order By: Relevance
“…and Cai et al . provided the STM images on vacuum co‐evaporated MAPbI 3 polycrystalline films (Figure d,e) in which similar dark protrusions were observed most likely corresponding to the I and/or I‐MA vacancies …”
Section: Defects In Metal Halide Perovskitesmentioning
confidence: 65%
See 1 more Smart Citation
“…and Cai et al . provided the STM images on vacuum co‐evaporated MAPbI 3 polycrystalline films (Figure d,e) in which similar dark protrusions were observed most likely corresponding to the I and/or I‐MA vacancies …”
Section: Defects In Metal Halide Perovskitesmentioning
confidence: 65%
“…It is likely that local properties on a much smaller scale, at the micrometer or even nanometer scale, are the key to settling many existing controversial issues in perovskite materials and solar cells . Since 2014, scanning tunneling microscopy and spectroscopy (STM/STS) have been used to investigate and correlate the structural and electronic properties at the atomic level . STM and STS can be used to visualize in real space defects at the atomic level and characterize their electronic properties on the perovskite surfaces (Figure f and Figure d,e).…”
Section: Defects In Metal Halide Perovskitesmentioning
confidence: 99%
“…Searching more immobilized and robust ligands or protective shells is imperative to gain solid‐state perovskite films with high quantum yields. Liu et al revealed that the pristine surface was robust, but if the defects occurred, e.g., vacancy, the perovskites were much easier to decompose starting from these defect points . The weak interaction between ligands and nanocrystals is easy to cause the formation of defects during film fabrication.…”
Section: Surface Engineeringmentioning
confidence: 99%
“…However, this raises the question of: how these defects will affect the physical properties of perovskite crystals. Liu et al revealed the influence of defects in the crystal, as discussed in Figure 10 [60]. Vacancy sites, V Br , V MA , V Br-Pb , and V Br-MA , can be formed easily when water molecules are adsorbed on the (010) surface of the CH 3 NH 3 PbBr 3 perovskite crystal because water reduces the formation energy of vacancy sites.…”
Section: Surface Structure Of Abx 3 Detecting By Stmmentioning
confidence: 99%